microRNA-4488 is differentially regulated during dengue virus infection and clearance of the virus - Filip, Roxana; Evers, Parrish; Uguccioni, Spencer M.; Alonzi, Rhea C.; Ahmed, Nadine; Ahmed, Noreen; Pezacki, John P. (Frontiers in RNA Research, 2025)
Dengue virus (DENV) is a zoonotic disease transmitted to humans via mosquito bites. Viral infection is systemic in humans and can lead to organ failure including in the liver. Since there are many molecular changes that precede liver failure, identification of progress at the molecular level is informative. As an RNA virus, DENV perturbs non-coding RNAs including microRNAs. Here we examine microRNA profiles in hepatoma cells using small molecule–mediated annotation of miRNA targets. It was previously shown that treatment with the broadly antiviral oxysterol 25-hydroxycholesterol (25HC) induces the expression of antiviral microRNAs in the liver. Herein, we show that 25HC is potently antiviral against Dengue virus and identify miR-4488 as a microRNA which is overexpressed during infection and downregulated with oxysterol treatment. We also show that miR-4488 is downregulated when the viral levels are lowered using siRNA, suggesting that this microRNA is involved in the host-response to infection. Since miR-4488 levels closely correlate with DENV levels in the liver, it serves as a biomarker for virus infection in the liver and may contribute the overall effects of DENV in this organ.